2017
DOI: 10.1098/rspb.2017.1583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution of insect immune memory versus pathogen resistance

Abstract: Under strong pathogen pressure, insects often evolve resistance to infection. Many insects are also protected via immune memory (immune priming), whereby sublethal exposure to a pathogen enhances survival after secondary infection. Theory predicts that immune memory should evolve when the pathogen is highly virulent, or when pathogen exposure is relatively rare. However, there are no empirical tests of these hypotheses, and the adaptive benefits of immune memory relative to direct resistance against a pathogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 41 publications
2
72
3
Order By: Relevance
“…Together, these results indicate that pathogen-mediated reduction in life span may impose strong selection for a priming response in natural populations, as predicted by theoretical models (Best et al, 2013) and observed in laboratory-evolved populations (Khan et al, 2017). Second, we found a life stage-specific negative relationship (a possible trade-off) with early reproductive success (measured over 2 days) that may constrain the strength of priming in adults, but not in larvae.…”
Section: Shirasucontrasting
confidence: 99%
See 4 more Smart Citations
“…Together, these results indicate that pathogen-mediated reduction in life span may impose strong selection for a priming response in natural populations, as predicted by theoretical models (Best et al, 2013) and observed in laboratory-evolved populations (Khan et al, 2017). Second, we found a life stage-specific negative relationship (a possible trade-off) with early reproductive success (measured over 2 days) that may constrain the strength of priming in adults, but not in larvae.…”
Section: Shirasucontrasting
confidence: 99%
“…Prior studies also show that priming alters bacterial load, though the timing (Tate, Andolfatto, Demuth, & Graham, ) and direction of the impact varies (compare Pham, Dionne, Shirasu‐hiza, & Schneider, ; Kutzer, Kurtz, & Armitage, ). Together, these results indicate that pathogen‐mediated reduction in life span may impose strong selection for a priming response in natural populations, as predicted by theoretical models (Best et al, ) and observed in laboratory‐evolved populations (Khan et al, ). Second, we found a life stage‐specific negative relationship (a possible trade‐off) with early reproductive success (measured over 2 days) that may constrain the strength of priming in adults, but not in larvae.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations